BMI, HYPERTENSION, AND DIABETES: A HEALTH PANORAMA IN GOIÁS (CIPEEX, 2025)
Obesity is a chronic metabolic disease, measured by BMI, which has been increasing worldwide and is associated with chronic diseases such as diabetes mellitus and hypertension. Nutritional transition and a sedentary lifestyle are key factors in the etiology of obesity, glycemic dysregulation, and hypertension. The objective of this study is to analyze the nutritional profile of hypertension and diabetes among adults in the state of Goiás in 2019. The methodology used 2019 data from SISVAN and PNS for statistical analysis, which included the calculation of the weighted average BMI and Pearson's correlation coefficient to assess the relationship between BMI and comorbidities, characterizing the study as an analytical retrospective observational one. The analysis demonstrated a high prevalence of obesity in adults in Goiás, with eutrophic (35.19%), overweight (33.47%), and obese (28.59%) individuals. A strong correlation was found between BMI and hypertension (0.92 for males and 0.99 for females) and diabetes (1.0 for males and 0.99 for females), indicating a robust linear relationship. A strong association was found between obesity and an increased prevalence of hypertension and diabetes in adults in Goiás.
Keywords: Non-communicable diseases; Diabetes; Hypertension